Producción del pimiento capsicum annuum mediante nutrición orgánica y mineral - Pacheco Díaz, Adrián Wilfrido (2009)
On the farmer Santa Inés of the Faculty of Agricultural Sciences of University of Máchala, studied the "Production of Peppers through Organic and Mineral Fertilization" Irazú long variety through the following objectives: Assess the production of pepper, trough the use of manures and fertilizers; establish the best or better treatment , nutrition resulting from, source of organic and mineral; realize a cost analysis for production of pepper, the levéis of fertility treatments were, three organics manures of the house Global Organic Biocharger 51/HA; Green Flish 4,0 I/HA; Mixsap F 0,5 I/HA), three levéis of NPK, 120-75-53; 160-100-70; 200-125-88 and a absolute witness.The evaluation of the treatments was performed by analyzing the following variables were determinants of agricultural production: loftiness plant to, to the 15, 30 and 60 days after of the transplant; number of fruits for plant; length and diameter of fruits; fruit weight and yield per plot. The treatments were applied to plots of 16 m2 arranged in Design randomized block, with seven treatments an four repetitions. The analysis of variance and mean comparison tests of Duncan with a significanee level of 1%, showed that fertilization with organic products and with NPK are the best treatments.The major production of fruits per plant and weight of fruits was achieved with levéis offruitfulness 160-100-70 and 200-125-88 of NPK. The organics manures in the dosagesapplied in foliar aspersión and the ground for the content of macro nutrients, hormones,amino acids, micro elements, reached productions increases of about of the 50% frontthe absolute witness and around of 90% with NPK. The highest yields with chemicalmanures was of 53 Ton/HA with the médium level, this is 160-100-70 of NPK and 40Ton with the organic mamare Mixsap F 0,5 I/HA. The higher profitability of the cropwent to the treatment five with the dosage 160-100-70 Kg. The second best treatmentwas the six with the dosage 200-125-88 Kg. The treatment that more income registeredwas of NPK in dosage of 160-100-70.